2016
DOI: 10.1002/2015pa002831
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature reconstructions over the last 70 kyr off Portugal: Biomarker data and regional modeling

Abstract: This study aims at providing robust temperature reconstructions for a key oceanographic setting in the North Atlantic and at understanding the nature of the temperature signal recorded by the two biomarkers U k′ 37 and TEX 86 , considering season and depth of production. To do so, high-resolution signals of U k′ 37 and TEX 86 are determined for the last 70 kyr for core MD95-2042, located off Portugal. Signals of U k′ 37 and TEX 86 present a tight correlation, demonstrating a dominant temperature effect. U k′ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(101 citation statements)
references
References 185 publications
(328 reference statements)
3
97
1
Order By: Relevance
“…In addition, alkenones and GDGTs are not analyzed in the same lipid extracts from MD99‐2348/PRGL1‐4 sediments. For example, using a single set of lipid extracts from the same depths of a sediment core from the Iberian Margin, Darfeuil et al () have reported an r coefficient of 0.89 ( n = 400, p < 0.001) between TEX 86 and U K′ 37 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, alkenones and GDGTs are not analyzed in the same lipid extracts from MD99‐2348/PRGL1‐4 sediments. For example, using a single set of lipid extracts from the same depths of a sediment core from the Iberian Margin, Darfeuil et al () have reported an r coefficient of 0.89 ( n = 400, p < 0.001) between TEX 86 and U K′ 37 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, alkenones and GDGTs are not analyzed in the same lipid extracts from MD99-2348/PRGL1-4 sediments. For example, using a single set of lipid extracts from the same depths of a sediment core from the Iberian Margin, Darfeuil et al (2016) have reported an r coefficient of 0.89 (n = 400, p < 0.001) between TEX 86 and U K′ 37 . An observation that is not reliant upon the resampling of previously published records is the systematic and coherent response of RI-OH to well-known climatic events.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in colder conditions and lower SSS in Heinrich Stadial 1 (HS1) with respect to the LGM (e.g. Cayre et al, 1999;Bard et al, 2000;Martrat et al, 2007;Eynaud et al, 2009;Voelker and Abreu, 2011;Darfeuil et al, 2016). In the Younger Dryas (YD) the protrusion of northern waters to the WIM was probably limited to subarctic waters (Eynaud et al, 2009), hence the YD was a cold and low SSS event compared to the B-A and Holocene, but not as much as during HS1.…”
Section: Paleoceanographic and Paleoclimatological Changes Across Thementioning
confidence: 99%